2017
DOI: 10.3233/bmr-150455
|View full text |Cite
|
Sign up to set email alerts
|

The recovery of damaged paraspinal muscles by posterior surgical treatment for patients with lumbar degenerative diseases and its clinical consequence

Abstract: There was reinnervation in not only denervated multifidus and erector spinae at 12 months following interspinous ligament stabilization but also in denervated erector spinae at 12 months following pedicle screw fixation with fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Cha et al noted denervated erector spinae muscles at 12 months following pedicle screw fixation with fusion. 36 This is closely related to postoperative long-term low back pain and in stabilization. Problems found in another study included nerve root or vascular injury due to instrumentation-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Cha et al noted denervated erector spinae muscles at 12 months following pedicle screw fixation with fusion. 36 This is closely related to postoperative long-term low back pain and in stabilization. Problems found in another study included nerve root or vascular injury due to instrumentation-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…The lumbar paraspinous muscle is of particular importance for the maintenance of stability and normal movement of spine [ 5 , 14 ]. Long incisions, extensive detachment of paraspinal muscles from the spinal processes, screws implant through multifidus muscle, and subsequently prolonged wide retraction can cause varying degrees of damage to paraspinous muscle, resulting in ischemic necrosis and denervation of the musculature in posterior lumbar surgery [ 7 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…As weight bearing begins and neurological improvement occurs, the observed changes may begin to revert to normal levels in response to the restoration of the normal biomechanics and anatomical alignment of the vertebral column. Many previous studies have highlighted the need for early rehabilitation and weight bearing (if possible) after the initial management of vertebral column injuries [11,12]. The limited strength observed in patients with SCI may be due to neurological factors or the insufficient muscle mass (more accurately, insufficient physiological muscle CSA) of neurally intact muscles.…”
Section: Discussionmentioning
confidence: 99%
“…By one way analysis of variance test. disease [12]. Postoperative computed tomography (CT) and MRI imaging studies have shown that reductions in the CSA of the spinal muscles occur, as well as changes in muscular density.…”
mentioning
confidence: 99%